2017
DOI: 10.1002/clen.201600678
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Stalks of DiatomDidymosphenia geminataas a Novel Biological Adsorbent for Hazardous Metals Removal

Abstract: The application of biomass derived from the nuisance fresh‐water diatom species Didymosphenia geminata toward the adsorption and removal of heavy‐metal ions from water is reported. The cell‐free polysaccharide‐based stalks of these diatoms are used as adsorbents to remove harmful metal ions: Pb(II), Ni(II), and Cd(II). Detailed analyses of the adsorption kinetics using both pseudo‐first‐order model and pseudo‐second‐order models are performed. The results show a strong correspondence to a pseudo‐second‐order k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…To investigate the type of adsorption mechanism for Fe­(III) and Cu­(II) of the lignin/chitin films, two kinetic models (pseudo-first-order and pseudo-second-order) were evaluated. ,, …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the type of adsorption mechanism for Fe­(III) and Cu­(II) of the lignin/chitin films, two kinetic models (pseudo-first-order and pseudo-second-order) were evaluated. ,, …”
Section: Methodsmentioning
confidence: 99%
“…Numerous research work toward the development of various technologies for the removal of toxic metal ions from water have been reported such as ion exchange resins, chemical precipitation and coagulation-flocculation, , electrolytic reduction, membrane technology, and biosorbents . Many alternatives with respect to fossil resource based solid-phase sorbents prepared from the renewable resources such as cellulose, lignin, and chitin have gained special attention. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the research surrounding D. geminata has focused on its structure, management, and possible negative impacts, there has been recent research published that demonstrates the possible positive effects that Didymo can have on the environment. In a paper written by Wysokowski et al [5], the authors state that the polysaccharide stalks of D. geminata have the ability to absorb harmful metal ions, such as Pb (II), Ni (II), and Cd (II). These stalks contain large amounts of complex extracellular biopolymers, which allows them to remove metals comparable to other polysaccharides.…”
Section: Benefits Of Didymomentioning
confidence: 99%
“…However, if the benefits of Didymo appear to outweigh its Their structure is considered to be helpful when it comes to metal removal applications due to the large amounts of complex extracellular biopolymers. Due to this characteristic, they are being considered as a fibrous absorbent of lead (II), nickel (II), and cadmium (II) in wastewater systems [5]. As more research was done on this species of algae, it was found that Didymo would be transferred to different parts of the river by sticking to the bottom of fishermen's boots.…”
Section: Introductionmentioning
confidence: 99%